2023
DOI: 10.1111/clr.14041
|View full text |Cite
|
Sign up to set email alerts
|

Early bone healing to implants with different surface characteristics. A pre‐clinical in vivo study

Abstract: Implant surface modifications are intended to improve conditions for osseointegration. Results from pre-clinical in vivo studies with focus on histological assessments of bone-to-implant contact or mechanical tests have shown superior results at implants with modified surfaces as opposed to implants with non-modified surfaces.On the other hand, observations made in pre-clinical studies have also indicated certain disadvantages with modified implant surfaces due to the potential risk for enhanced progression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Surface roughness has not been proved to prevent MBL [ 76 , 77 ] nor the onset of peri-implantitis [ 78 ], but patient-related factors such as a history of periodontitis and smoking are deemed to be more clinically important for MBL [ 79 ]. Surprisingly, recently, in a pre-clinical model, it has been suggested that acid-etched surfaces enhance the early formation of bone-to-implant contact [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surface roughness has not been proved to prevent MBL [ 76 , 77 ] nor the onset of peri-implantitis [ 78 ], but patient-related factors such as a history of periodontitis and smoking are deemed to be more clinically important for MBL [ 79 ]. Surprisingly, recently, in a pre-clinical model, it has been suggested that acid-etched surfaces enhance the early formation of bone-to-implant contact [ 80 ].…”
Section: Discussionmentioning
confidence: 99%